IS DOUBLE SALARY ENOUGH?: EXAMINING CIVIL SERVANT TEACHERS' WELFARE AS THE EFFECT OF TEACHER CERTIFICATION POLICY IN INDONESIA - Bismo, Pandu Ario; Chozin, Muhamad Nur; Adem, Angela Merici Girlani; Muljawan, Hanna Raisya (Natapraja, 2024)
Teacher quality is a critical determinant of student achievement and overall educational success. In Indonesia, the enactment of the Teacher and Lecturer Law in 2005 marked a significant effort to improve teachers’ welfare through the Teacher Professional Allowance (Tunjangan Profesi Guru/TPG), which specifically doubles teachers’ income after certification. The policy faces persistent challenges despite its intent, including failure to meet certification targets and limited impact on student learning outcomes. This study examines the effects of the current teacher certification on teachers’ welfare in Indonesia. Employing a desk research method, the research highlights that while TPG contributes positively to teachers’ welfare and motivation, clearly it is still not enough to make teaching a respected profession in Indonesia. Broader systemic issues, such as disparities in earnings, contract-based employment, and the need for additional income, undermine its effectiveness. The findings suggest that teacher certification policies must be refined to ensure equitable and sustainable improvements in teachers’ welfare. This study contributes to limited research on teacher certification and welfare, offering recommendations for more effective policy.